Factors influencing travel intention in the midst of Covid-19 pandemic at Kawasan Kuliner Pasar Lama, Tangerang - Vimutti Hasita Lourent Jinarakkhita; Dedi Kurniawan (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Tourism has been one of the sectors hardest hit by the coronavirus outbreak, with many tourist destinations empty. As countries around the world enforced travel restrictions and the introduction of large-scale social regulations (PSBB) forced people to stay at home in Indonesia. The pandemic has changed the order of social life and society. Among those most affected are the economic and tourism sectors including Kawasan Kuliner Pasar Lama in Tangerang City. The purpose of this study is to find out the influence of Knowledge of COVID-19, Knowledge of Tourism, Tourist Experience towards Travel Intention to Kawasan Kuliner Pasar Lama. This study uses a quantitative research method with survey technique. The respondents are selected using the technique of non-probability sampling especially purposive sampling. The questionnaire were filled up by 301 people who have already experienced visiting and are familiar with Kawasan Kuliner Pasar Lama. The data collected was analyzed with the structural equation model. From the analysis result, this study found that Knowledge of COVID-19 has no influences Attitude of Risk Aversion, Knowledge of Tourism has influences Attitude of Risk Aversion, Tourist Experience has influence Destination Image, Attitude of Risk Aversion has negatively influences Travel Intention, Destination Image has influences Travel Intention. The managerial implications of this study The government and management center can give more socialization about COVID-19 to the owner of the store/restaurant and visitors. Government and management centers can train the owner store/employee of food stalls/street vendors/labor worker. Meanwhile, from theoretical implications This study analyzes the correlation between Knowledge of COVID-19, Knowledge of Tourism, and Tourist Experience as independent variables with Attitude of Risk Aversion, Destination Image, and Travel Intention as dependent variables.